Accountability, transparency and court organization in Spanish civil justice - de Benito, Marco (Civil Procedure Review, 2023)
The article essentially reproduces the Spanish national report for the session on accountability and transparency in civil justice held at the XVI World Congress on Procedural Law, held in Japan in 2019. As such, its main aim was and is to facilitate comparative scholarship by presenting, in a brief yet accurate manner, the legal framework and practical implications of judicial accountability and transparency in Spanish civil justice, with a reference to relevant aspects of the overall civil court system. An important tenet of judicial independence, in Spain judicial accountability is made effective by means of a comprehensive system of civil, disciplinary, and administrative individual and state responsibility, as well as by a growingly detailed and accessible system to ensure transparency at all levels of the judiciary